Shift from flooding to drying enhances the respiration of soil aggregates by changing microbial community composition and keystone taxa - Zhu, Kai; Jia, Weitao; Mei, Yu; Wu, Shengjun; Huang, Ping (Frontiers in Microbiology, 2023)
Changes in the water regime are among the crucial factors controlling soil carbon dynamics. However, at the aggregate scale, the microbial mechanisms that regulate soil respiration under flooding and drying conditions are obscure. In this research, we investigated how the shift from flooding to drying changes the microbial respiration of soil aggregates by affecting the composition of microbial communities and the frequency with which different types of microbes coexist together. Soils collected from a riparian zone of the Three Gorges Reservoir, China, were subjected to a wet-and-dry incubation experiment. Our data illustrated that the shift from flooding to drying substantially enhanced soil respiration for all sizes of aggregate fractions. Moreover, soil respiration declined with aggregate size in both flooding and drying treatments. The keystone taxa in bacterial networks were found to be Acidobacteriales, Gemmatimonadales, Anaerolineales, and Cytophagales during the flooding treatment, and Rhizobiales, Gemmatimonadales, Sphingomonadales, and Solirubrobacterales during the drying treatment. For fungal networks, Hypocreales and Agaricalesin were the keystone taxa in the flooding and drying treatments, respectively. Furthermore, the shift from flooding to drying enhanced microbial respiration of soil aggregates by changing keystone taxa. Notably, fungal community composition and network properties dominated the changes in microbial respiration of soil aggregates during the shift from flooding to drying. Thus, our study highlighted that the shift from flooding to drying changes keystone taxa, hence increasing aggregate-scale soil respiration.